Metastatic cutaneous squamous cell carcinoma accounts for nearly all squamous cell carcinomas of the parotid gland. - Bradley, Patrick J.; Stenman, Göran; Thompson, Lester D.R.; Skálová, Alena; Simpson, Roderick H.W.; Slootweg, Pieter J.; Franchi, Alessandro; Zidar, Nina; Nadal, Alfons; Hellquist, Henrik; Williams, Michelle D.; Leivo, Ilmo; et al. (Virchows Archiv, 2024)
Primary squamous cell carcinoma of the parotid gland (pSCCP) has long been recognized as a separate entity and is included in the WHO classifications of salivary gland tumors. However, it is widely accepted among head and neck pathologists that pSCCP is exceptionally rare. Yet, there are many publications describing series of pSCCP and data from SEER and other cancer register databases indicate erroneously an increasing incidence of pSCCP. Importantly, pSCCP and metastatic (secondary) squamous cell carcinoma to the parotid gland (mSCCP) have nearly identical histological features, and the diagnosis of pSCCP should only be made after the exclusion of mSCCP. Moreover, all of the histological diagnostic criteria proposed to be in favor of pSCCP (such as, for example, dysplasia of ductal epithelium) can be encountered in unequivocal mSCCP, thereby representing secondary growth along preexistent ducts. Squamous cell differentiation has also been reported in rare genetically defined primary parotid carcinomas, either as unequivocal histological squamous features (e.g., NUT carcinoma, mucoepidermoid carcinoma), by immunohistochemistry (e.g., in NUT carcinoma, adamantinoma-like Ewing sarcoma, basal-type salivary duct carcinoma, mucoepidermoid carcinoma), or a combination of both. Another major issue in this context is that the International Classification of Diseases (ICD) coding system does not distinguish between primary or metastatic disease, resulting in a large number of patients with mSCCP being misclassified as pSCCP. Immunohistochemistry and new molecular biomarkers have significantly improved the accuracy of the diagnosis of many salivary gland neoplasms, but until recently there were no biomarkers that can accurately distinguish between mSCCP and pSCCP. However, recent genomic profiling studies have unequivocally demonstrated that almost all SCCP analyzed to date have an ultraviolet light (UV)-induced mutational signature typical of mSCCP of skin origin. Thus, mutational signature analysis can be a very useful tool in determining the cutaneous origin of these tumors. Additional molecular studies may shed new light on this old diagnostic and clinical problem. This review presents a critical view of head and neck experts on this topic.
EVALuna2:568045